The Origins of the Arabic Language: From Silence to Speech, Tracing the Earliest Origins of Human Language - Fitria, Annisa Rahma; Aninda, Dina Putri; Sulton, Zannuba (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Arabic is one of the Semitic languages that has developed over thousands of years. Arabic emerged as an independent language because early Semitic language speakers migrated and formed their own language and nation. The interaction between Arabic and local languages led to the formation of the original Arabic language with various dialects. Arabic has been able to grow and develop independently due to many factors, one of which is social interaction and the intermingling of different nations. Arabic is one of the most widely used languages in the world, making it important to understand its history. The origin of human language has long been a mystery that fascinates scholars from various disciplines, including linguistics, anthropology, archaeology, and genetics. This article aims to explain the origins of the Arabic language based on existing theories. The method used in this research is a library study, which involves reading relevant literature. The study results indicate that Arabic comes from the Semitic language family (which includes Hebrew, Aramaic, and Akkadian). The early development of Arabic took place in the Arabian Peninsula, where it was initially used by nomadic tribes in the region. The influence of the Qur'an became a primary reference in the development of Arabic grammar and vocabulary.